Sustainability of one-time seed distributions: a long-term follow-up of vegetable seed kits in Tanzania - Wanyama, Rosina; Mvungi, Henry; Luoga, Ritha; Mmasi, Maria; Zablon, Ernest; N’Danikou, Sognigbe; Schreinemachers, Pepijn (Frontiers in Sustainable Food Systems, 2023)
The one-time distribution of vegetable seed kits containing small (2 grams) samples of improved varieties of traditional and exotic vegetables can potentially increase vegetable production and consumption among poor rural households, but evidence is lacking. This study therefore analyzed the extent to which recipients of vegetable seed kits in Tanzania have sustained the use of introduced vegetable varieties. Data came from a random sample of 796 households who directly or indirectly received seed kits between 2012 and 2018, complemented with 10 focus group discussions among seed kit recipients. The results show that 24% of direct recipients are still reproducing the seed of introduced vegetable varieties after a period of 5–10 years, with variation across varieties and the time seed was introduced. The success rate was higher for traditional vegetables than exotic vegetables and higher for women than men. Reasons for not continuing seed use were the lack of knowledge on seed saving, problems with pests and diseases, and reduced germination. Hence, the sustainability of small seed kit distributions can be enhanced by accompanying them with adequate training on seed saving and seed storage.